Avascular necrosis of the hip in a man with HIV infection. Issue 6 (December 1990) - Goorney, B P; Lacey, H; Thurairajasingam, S; Brown, J D
Abstract : The development of an osteonecrotic (avascular necrosis) hip joint in a patient with symptomatic CDC Stage 1V C2 disease is reported. The diagnosis was aided by radiological assessment and confirmed by radioisotope bone scan. This case serves as yet another musculoskeletal manifestation in association with HIV infection.